Sleep Disturbances in Individuals with Alcohol-Related Disorders: A Review of Cognitive-Behavioral Therapy for Insomnia (CBT-I) and Associated Non-Pharmacological Therapies - Brooks, Alyssa T (Libertas Academica, 2014)
Sleep disturbances are common among alcohol-dependent individuals and are often associated with relapse. The utility of behavioral therapies for sleep disturbances, including cognitive-behavioral therapy for insomnia (CBT-I), among those with alcohol-related disorders is not well understood. This review systematically evaluates the evidence of CBT-I and related behavioral therapies applied to those with alcohol-related disorders and accompanying sleep disturbances. A search of four research databases (PubMed, PsycINFO, Embase, and CINAHL Plus) yielded six studies that met selection criteria. Articles were reviewed using Cochrane’s Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) scoring system. A majority of the studies demonstrated significant improvements in sleep efficiency among behavioral therapy treatment group(s), including but not limited to CBT-I. While behavioral sleep interventions have been successful in varied populations, they may not be utilized to their full potential among those with alcohol-related disorders as evidenced by the low number of studies found. These findings suggest a need for mixed-methods research on individuals’ sleep experience to inform interventions that are acceptable to the target population.